Kinetika pembentukan struvite kristal menggunakan zeolit alam sebagai adsorben pada aeration cone column crystallizer - Eko Ariyanto; Yuyun Niyati; Dian Kharismadewi; Robiah (Jurnal Rekayasa Proses, 2020)
Wastewater from the fertilizer industry contains a high concentration of PO43- and NH4+. Those ions formed deposits that frequently clogged the conduits and reduced the pump efficiency of the wastewater treatment plant. A high concentration of PO43- and NH4+ in this wastewater can be used as a secondary source of PO43- fertilizer through the recovery process into struvite compounds (MgNH4PO4.6H2O). In this research, Struvite was crystallized in Aeration Cone Column Crystallizer (ACCC) with Magnesium modified natural Zeolite (Zeo-Mg) as adsorbent. Research also has been done using the Batch process, and the results were used as basis variables in the ACCC system. Effects of Zeolite activation, amounts of Zeo-Mg (10 – 30 g), PO43- and NH4+reactant ratio (1:1 – 1:3), pH (6 – 9), and reaction time (0 – 60 minutes) to the removal percentage of PO43- were used as research parameters that analyzed in struvite crystallization process. Zeo-Mg and struvite produced were analyzed using scanning electron microscopy and energy dispersive X-ray spectroscopy. Research results in the ACCC system with Zeo-Mg as adsorbent showed that the percentage of PO43- removal was 65% in 16 minutes and followed pseudo-first-order reaction kinetics with a reaction rate constant of 0.21 min-1. The PO43- removal reached equilibrium at pH 8.10 after 28 minutes. Simultaneous removal of PO43- to formed struvite crystals using Zeo-Mg as an adsorbent and without the addition of Mg ions solution in the ACCC system is a novel process in wastewater treatment. Moreover, this PO43- recovery process can be implemented in the industrial scale due to the practical operation.